A belated boom: Uganda, Kenya, South Sudan, and prospects and risks for oil in East Africa - Luke A. Patey (The Oxford Institute for Energy Studies, 2017)
East Africa has followed a long road of highs and lows in developing its oil resources. On the back of high global oil prices between 2004 and 2014, a rush of new exploration put the region on the map as a new frontier for African oil. But it did not take long for the momentum of East Africa's oil rush to lose steam. Long regulatory delays, security risks, and the fall of global oil prices, all served to deflate expectations for the region's potential. This paper examines the development, potential, and main risks facing oil industries in Uganda, Kenya, and South Sudan, as well as plans for regional pipelines in East Africa. It finds that beyond the impact of domestic political and security conditions, what defines the emergence of East Africa as a new African energy centre is the growing influence of regional politics.
Keywords: 330